Expectant management of patients with unilateral hepatic duct stricture and liver atrophy. Issue 10 (October 1986) - Hadjis, N S; Carr, D; Blenkharn, I; Banks, L; Gibson, R; Blumgart, L H
Abstract : Three patients with postcholecystectomy unilateral hepatic duct stricture and subsequent liver atrophy were treated conservatively, with a successful outcome of up to three years follow up. A better understanding of the pathophysiological sequelae of segmental hepatic duct obstruction suggests that in such circumstances reconstructive surgery, with its attendant risks, may not invariably be necessary.